Clinical follow-up at 18 months of two Bulk Fill occlusal composite resins. A double-blind randomized clinical study. - Patricio Vildósola Grez; Sara Rodriguez Dueri; Jenifer Carrión; Constanza Saez; Jorge Nakouzi Momares (Universidad de Concepción., 2022)
Objetive: To compare the clinical behavior of two types of Bulk Fill composite resins and a nanohybrid resin at 18 months in occlusal restorations. Material and Methods: Three occlusal restorations were performed in each one of the 55 participants. They were randomly distributed into three groups, TN: Tetric-N-Ceram Bulk-Fill, FK: Filtek Bulk-Fill, and Z350: Filtek Z350XT. Adhesive techniques and restorative procedures were performed according to the manufacturer's instructions for each restorative material used. In TN and FK an increment of 4mm was applied, and in Z350 increments of ≤2mm depth were applied. Two calibrated operators evaluated the restorations at baseline and at 18 months using the FDI World Dental Federations system (1: excellent, 2: good, 3: satisfactory, 4: unsatisfactory, 5: poor) for clinical marginal staining (MS) properties, fracture-retention (FR), superficial texture (ST), marginal integrity (MI), postoperative sensitivity (PS) and caries (C). Kruskal-Wallis and Wilcoxon were used to compare the 3 groups at 18 months (5% significance). Results: 38 patients with a total of 114 restorations were assessed, being evaluated with excellent clinical behavior; MI, 78.9% in Z350, 89.51% in TN and 81.6% in FK; ST 73.5% in Z350, 86.8% in TN, and 84.2% in FK; MS 84.2% in Z350, 84.2% in TN, and 91.2% in FK; PS 100% in Z350 and 97.3% in TN and FK; in C and FR, 100% in the 3 groups. There were no significant differences between the three groups (p>0.05). Conclusion: The three resins studied presented a good clinical performance at 18 months without showing significant differences in the clinical properties evaluated.